Connection of a Steel Column Base Plate: Mechanical Behavior and Stiffening Effects - Benyelles Chemseddine Mehdi; Nadir Boumechra; Abdelghani Missoum; Abdelhamid Bouchair (Civil Engineering Journal, 2022)
This paper investigates the behaviour of a steel column base connection subjected to a bending moment and compressive axial force. The behaviour of this connection is quite complex due to the number of components, such as the base plate, anchor rods, and stiffeners, to be considered in the numerical models. Moreover, a nonlinear three-dimensional finite element model was used to simulate the column base connection. This model can be used to analyze the moment-rotation relationship for the connection through the validation of numerical modeling with those given by the experimental test results and compared with the analytical model based on the components method of Eurocode 3. It was shown that in addition to the stiffness and bending resistance of the column base connection, other mechanical parameters, such as moment-rotation shape, stress distribution, and prying actions, can be significantly influenced by changing the properties of the components. It has been demonstrated that the anchor rod is not only affected by the axial force but also by a local moment that is not taken into consideration by the analytical model of Eurocode3. An extensive parametric study on stiffeners showed very interesting effects obtained by adding the welded stiffeners to the column base connections. Doi: 10.28991/CEJ-2022-08-09-02 Full Text: PDF